Development of Science Learning Tool Based on Problem Based Learning with Google Classroom to Improve Argumentation Skill - Ade Cyntia Pritasari; Jumadi Jumadi (Biosaintifika: Journal of Biology & Biology Education)
Using science learning tools will optimize the learning process. Good learning process will train the skill needed in the 21st century, including the skills of argumentation. From this point of view, an science learning tool based on problem based learning with google classroom has developed in this study. This study aimeds to test the appropriateness of science learning tool and the effectiveness of science learning tool developed in improving argumentation skill. This study was an research and development (R&D) research using 4D method from Thiagarajan with four stages including define, design, develop, and disseminate. The product trials have been conducted in 7th grade students of State Junior High School 2 Magelang at second semester of year 2017/2018. The data collection was done by non-test and test technique. Based on the results of the research note that learning tools developed theoretically declared valid based on expert assessment with very good category and effective in improving students’ argumentation skill. Learning tool based on problem based learning with google classroom is a new approach to learning with the capability to the transform education in a better quality. Implementation of learning tool based on problem based learning with google classroom provide new alternatives in improving the quality of science education achievement.